Polycentric urban development in China: A multi-scale analysis - Liu, Xingjian; Derudder, Ben; Wang, Mingshu (Environment and planning. B, Urban analytics and city science, 2018)
This article reports a multi-scale analysis of polycentric urban development in 22 Chinese city-regions. Using fine-grained population data, our analysis contrasts polycentric development patterns at multiple geographical scales. We present a typology of Chinese city-regions based on both (1) their inter-city polycentricity and (2) the intra-city polycentricity of the individual cities that comprise these urban regions. Overall, we find only limited levels of association between inter-city and intra-city polycentricity. The Pearl River and Yangtze River Deltas have high levels of inter-city and intra-city polycentricity. Most city-regions in Central and Western China are characterized by a primate urban system and low levels of inter-city polycentricity. We hypothesize the major economic, political, and geographical processes underlying observed patterns.